Krisis Pelarian dalam Hubungan Vietnam Utara dengan Thailand, 1954-1975 : The Refugee Crisis in North Vietnam’s Relations with Thailand, 1954-1975 - Husin, Ahmad Zainudin (SEJARAH: Journal of the Department of History, 2022)
This article aims to analyse the issues following the presence of Vietnamese refugees in Thailand during the War (1954–1975). The focus of the analysis is on Thailand’s attitude towards Vietnamese refugees as well as the steps taken to return the refugees to Vietnam. This research uses qualitative methods, particularly document analysis, emphasising the use of British official government documents, newspapers that were published in South Vietnam and Thailand, books, and scientific articles. The findings of this study show that the presence of Vietnamese refugees during the Vietnam War created restlessness among the leaders and people of Thailand. Apart from security issues, their presence also invites social problems in Thailand. At the time, the refugee repatriation effort was carried out successfully. Still, it was thwarted by the presence of a second more enormous wave following the failure of South Vietnam to defend its country. This caused the issue to continue until the 1990s, despite Thailand’s involvement in helping the United States army defend South Vietnam during the Vietnam War 1964-1975, efforts to resolve the refugee issue are still overshadowed by the country’s cold relationship with Vietnam. Received: 26 September 2022 Reviewed: 12 October 2022 Accepted: 7 December 2022